From Big Data to Dataism: Philosophical Reflections on Freedom, Labor, and Biological Inequality from a Historical Materialist Perspective - Hạnh, Nguyễn Vân (Philosophy and Realistic Reflection, 2026)
Grounded in the methodology of historical materialism, the article interprets dataism as a new configuration of power and ownership emerging within the digital mode of production. While big data technologies significantly enhance economic efficiency and scientific knowledge, they also generate structural risks for future society. The study analyzes four interrelated concerns. First, the concentration of data ownership may facilitate forms of algorithmic governance that threaten democratic institutions and individual autonomy. Second, the rapid development of artificial intelligence could restructure labor markets, leading to large-scale displacement and deepening socio-economic inequality. Third, the convergence of biotechnology and data analytics raises the possibility of biological stratification through genetic intervention. Fourth, personalized data profiling may intensify individualized forms of discrimination. Taken together, these developments suggest that dataism challenges not only distributive arrangements but also the normative foundations of freedom, equality, and human agency. The article argues that these risks require philosophical reflection and institutional responses aimed at preserving democratic autonomy and a shared human condition. Such responses include democratic oversight of data ownership, investment in education and human development, and the establishment of global legal–ethical frameworks for emerging genetic technologies.